OPTIMIZATION OF Bacillus sp. K29-14 CHITINASE PRODUCTION USING MARINE CRUSTACEAN WASTE - Agustinus Robert Uria; Ekowati Chasanah; Yusro Nuri Fawzya (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Chitin is present in large quantities in the marine crustacean waste disposed by seafood processing industries, making it very desirable as the substrate for producing chitinase, a hydrolytic enzyme of considerable interest in many industrial and agricultural applications. In our work, crustacean waste powder and its combination with colloidal chitin at different concentrations (0.5, 1.0, and 1.5%) were utilized to optimize the chitinase production by the bacterium, Bacillus sp. K29-14. The results showed that the chitinase production with the three different substrate concentrations was relatively constant in the range of 0.2 to 0.3 U/ml during 12 days cultivation, although there was a bit reduction after day 8. This activity profile seems to be similar to that of the protein content. Whereas the chitinase production on the media containing crustacean waste powder and its combination with colloidal chitin at the three concentrations showed that the highest activity (3.0 to 4.6 U/ml) was achieved on day 7 and 8. The specific chitinase activity with the waste powder at different concentrations of substrate (0.5, 1.0 and 1.5%) was increasing slowly during a nine-day cultivation. The optimal chitinase production (4.6 U/ml) was achieved with the combined substrate of 0.5% on day 8.